Pediatric infection with the Omicron variant increases the risks of febrile seizures among COVID-19 infected children - Mohamed, Zakaria Ahmed; Tang, Chunjiao; Thokerunga, Erick; Deng, Youping; Fan, Jingyi (Frontiers in Pediatrics, 2023)
Background The Omicron variant of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is less likely to cause severe disease in children than the other variants but has become an increasing cause of febrile seizures (FS) among children. In this case-control study, we aimed to examine the risk factors associated with FS in children infected with the COVID-19 Omicron variant and related treatment modalities. Methods This retrospective case-control study includes 113 subjects infected with the COVID-19 Omicron variant, grouped into 45 cases (those with FS) and 68 controls (those without FS). Data on clinical features, laboratory parameters, and treatment modalities were collected and analyzed. Results Approximately 5.74% of COVID-19 infected children developed COVID-19-associated FS. Children with COVID-19 and high body temperatures [RR 1.474; (95% CI: 1.196–1.818), p < 0.001], previous history of FS [RR 1.421; (95% CI: 1.088–1.855), p = 0.010], high procalcitonin levels [RR 1.140; (95% CI: 1.043–1.246), p = 0.048] and high neutrophil counts [RR 1.015; (95% CI: 1.000–1.029), p = 0.048] were more likely to experience FS than the controls. In contrast, children with COVID-19 and low eosinophil counts, low hemoglobin levels, and cough had a lower risk of developing FS [RR 0.494; (95% CI: 0.311–0.783), p = 0.003], [RR 0.979; (95% CI: 0.959–0.999), p = 0.044]; and [RR 0.473 (95% CI 0.252–0.890), p = 0.020]; respectively. Children with FS received more anti-flu medications than those without. Conclusion A significant increase in FS was observed in children with Omicron SARS-CoV-2 infection. A higher body temperature, a history of FS, a higher procalcitonin level, and a high neutrophil count were all associated with an increased risk of FS in children with COVID-19. The risk of developing FS was lower in children with COVID-19 and low eosinophil counts and hemoglobin levels than in those without.